Automated Test Data Generation for Embedded System Models Using Combinatorial Testing - Ngoc, Do Thi Bich (Journal of Science and Technology on Information security, 2023)
Abstract— Embedded systems have been playing very important roles in modern society. They have appeared in every aspect of life from automotive to avionics industries to home appliances, etc. These embedded systems therefore must satisfy high quality requirements. As a consequence, quality assurance for these kinds of systems has attracted much attention and investment from both academic research and industry communities. In developing embedded systems, testing often requires high coverage with different measures with respect to international standards like Decision Coverage (DC), Condition Coverage (CC), Modified Condition/Decision Coverage (MC/DC) respected to ISO 26262. However, it is difficult to generate test cases with high coverage due to the complexity of the embedded system, the larger number of inputs, and the complex continuous signals of inputs. In order to have good test cases with high DC, CC, MC/DC coverage measures, this paper proposes a method to automatically generate test-cases by applying Combinatorial testing technique. The requirements of the inputs of the embedded model will be encoded to the input of Combinatorial testing technique in order to generate test cases that cover all pair values of any two inputs. Experiments on case studies showed that proposed method has coverage result better than that of the random testing method.